A study on the oral health awareness of UPCD students batch '87 to '90 - Umali, Irenne
This study was done to determine if the principles and theories learned in the UPCD has any influence on the individuals oral health awareness and to find out of there is any difference in awareness among different year levels knowing that the higher years have taken more dental subjects. As a result of the survey done for this purpose, the researchers got the conclusion that the principles and theories learned in the college has a influence on the individuals oral health awareness and that the awareness level among the year levels does not differ even though the higher years have taken more dental subjects.